Implementation of Standard Operating Procedures for Patient Care - Umar Sako; Zulkarnain Lababa (Journal La Sociale, 2022)
This study aims to determine the application of standard operating procedures for patient care in the emergency room of dr. MM. Dunda Limboto, Gorontalo District. The research method used is a qualitative research approach with descriptive research type. The results showed that the Application of Standard Operating Procedures (SOP) for Patient Services in the IGD RSUD dr. MM. In general, Dunda Limboto Gorontalo District has not been implemented optimally. This can be seen from the 7 SOP indicators, only 4 have been implemented properly. As for the results of the research on these indicators are: 1) the procedure for registering patients in the ER has not been running optimally, 2) the procedure for receiving patients in the patient reception room has not been optimally carried out, 3) The doctor prepares for the examination including: Patient preparation , tools, washing hands and wearing PPE, the results of the study found that this procedure was carried out well, 4) The doctor carried out the examination including: history taking, physical examination and checking the patient's vital signs, supporting examinations, had not been carried out properly, 5) The doctor determined the diagnosis meanwhile, it has been carried out properly, 6) The doctor determines the treatment and medical action on the patient, this procedure has been carried out in accordance with the SOP, and 7) The doctor observes and evaluates the results of treatment or action, this procedure has been carried out in accordance with the existing SOP.